Trends in the innovative development of smart cities - E. A. Smirnov; V. G. Kashtanov; V. V. Denk; E. A. Khalimon (Вестник университета)
The article studies examples of the use of innovative technologies in the field of “Smart City”, which is a key factor contributing to the implementation of the concept of “Smart City”. The paper presents various approaches to the implementation of information technologies, analyses case studies on the management of smart cities of the world, which justify the change in the approach from isolated vertical management to integrated holistic management. The study also analyses various examples of the use of innovative technologies and approaches in the context of “Smart City”, identifies the trends in their development. At the end, the authors carried out the analysis of the domestic experience of applying the concept of “Smart City” and the results achieved.